Climate, Land Use, and Landscape Change in Southern Bilad al-Sham (Northern Jordan) during the Islamic Periods - Lucke, Bernhard (Journal of Islamic Archaeology, 2018)
Common narratives of "decline" in Jordan and Syria during the Islamic periods are based on diminishing evidence for construction and maintenance of monumental architecture, and often consider man-made degradation of the environment, such as soil erosion due to mismanagement, as a key factor of reduced productivity. This contribution tackles the question of historic landscape change with a case study of the site of Abila in northern Jordan, and reviews the literature on the matter. Sediments in the Wadi Queilbeh near Abila suggest that two periods of rapid and significant deposition took place during the 6th and 14th-15th centuries AD, which were connected with extreme rainfalls induced by global climate fluctuations. As well, a general trend to drier conditions is discernible after the 6th century. Other periods are characterized by absence of sedimentation, and soil distribution in the vicinity suggests stable and fertile conditions where water availability determines the agricultural potential. Changes of settlement and environment can be explained with reduced rainfalls during the Islamic periods that led to a diversification of land use from market-oriented agriculture towards subsistence farming. This reduced surpluses and thus less monumental buildings were built. The practice of a mixed economy with an increasing share of pastoralism was connected with natural reforestation of some areas, and seasonal use of many areas may have led to incorrect perceptions of "empty" lands by European travelers. Tribes settled when they could realize the benefits of agriculture. Climate fluctuations most likely represent the underlying drivers of environmental and economic changes in northern Jordan during the Islamic periods.
CRIS-Team WoS Importer:2019-03-15